2020
DOI: 10.1109/access.2020.2992794
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Adaptive Locomotion Control System for Online Adaptation of a Walking Robot on Complex Terrains

Abstract: Developing a controller that enables a walking robot to autonomously adapt its locomotion to navigate unknown complex terrains is difficult, and the methods developed to address this problem typically require robot kinematics with arduous parameter tuning or machine learning techniques that require several trials or repetitions. To overcome this limitation, in this paper, we present continuous, online, and self-adaptive locomotion control inspired by biological control systems, including neural control and hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Furthermore, it is critical that the robot be self-learning for better path planning when negotiating obstacles in an unknown cluttered environment. In the future, we intend to use a neural controller [38], [39,41] to coordinate all the sensorimotor processes simultaneously. It will involve self-learning for autonomous crawling and the appropriate selection of gaits, depending on the surface, and the desired locomotion type (crawling, climbing, obstacle avoidance, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is critical that the robot be self-learning for better path planning when negotiating obstacles in an unknown cluttered environment. In the future, we intend to use a neural controller [38], [39,41] to coordinate all the sensorimotor processes simultaneously. It will involve self-learning for autonomous crawling and the appropriate selection of gaits, depending on the surface, and the desired locomotion type (crawling, climbing, obstacle avoidance, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…While Walknet control shows impressive performance for versatile and adaptive robot behavior generation (locomotion and object manipulation), it may lead to unstable robot behavior or failure in cases of sensory failure. Therefore, a combination of CPG-and reflex-based control has been actively investigated and various types of this combination have been developed [142,[197][198][199][200][201][202][203]. For instance, CPG-based control with a sensory event mistiming detection method and reflexes was proposed [201].…”
Section: Bio-inspired Controlmentioning
confidence: 99%
“…This robot can still perform basic locomotion even without the sensory feedback. Recently, an artificial hormone mechanism (AHM) was applied to the adaptive neural locomotion control [202,203]. AHM, which replicates the endocrine system, can continuously online adapt neural locomotion control parameters (lifelong continuous adaptation) for walking on different complex terrains (e.g., mesa terrain, ramp-up and -down terrains, rough terrain, terraced terrain, compliant terrain with different softness levels, and loose terrain).…”
Section: Bio-inspired Controlmentioning
confidence: 99%
“…For another example, Owaki et al proposed a simple CPG model where one phase oscillator controls each limb's stride motion and demonstrated that phase modulations depending on loads of limbs contribute to generating various gaits locomotion speed and leg amputation (Owaki et al, 2017 ). Regarding adaption to uneven environments, however, previous models still require recruiting a large number of neural components for modulating interlimb coordination depending on situations (Durr, 2001 ; Bläsing, 2006 ; Schilling et al, 2013a , b ; Ngamkajornwiwat et al, 2020 ). This is because the limb without a stable foothold should adaptively change its foot trajectory and frequency comparing other limbs to search steady footholds.…”
Section: Introductionmentioning
confidence: 99%